The Influence of Psychological Capital on Work Readiness in Diploma Level Undergraduates at Padang State University with Gender as A Moderating Variable - Augesty Fadhilah Putri; Farah Aulia (Causalita, 2024)
The percentage of unemployed at the diploma level is higher than at the undergraduate level, even though diploma-level students have skills that undergraduate students do not get. It shows the lack of work readiness of diploma-level students. One of the factors that influences work readiness is psychological capital. Furthermore, one of the factors that can influence psychological capital and work readiness is gender. This research aims to see whether gender can moderate the influence of psychological capital on work readiness in final diploma-level students at Padang State University. This research uses a quantitative approach. The number of samples in this study was 100 final diploma-level students at Padang State University who were selected using the proportionate stratified random sampling technique. Data was collected using a work readiness scale with a reliability of 0.821 and a psychological capital scale with a reliability of 0.813. Data analysis in this research used moderated regression analysis using the subgroup method. This research shows that gender cannot moderate the influence of psychological capital on work readiness in final diploma-level students at Padang State University.